2010
DOI: 10.1016/j.jvs.2010.02.281
|View full text |Cite
|
Sign up to set email alerts
|

Below knee bare nitinol stent placement in high-risk patients with critical limb ischemia is still durable after 24 months of follow-up

Abstract: The 2-year outcome of our series underscores the value of infrapopliteal nitinol stent placement as a durable bailout treatment option in high-risk CLI patients with suboptimal angioplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 14 publications
1
20
0
1
Order By: Relevance
“…Bare nitinol self-expanding stents are currently used to treat suboptimal angioplasty results in infrapopliteal disease. A nonrandomized retrospective study of 53 patients with CLI and infrapopliteal disease (Rutherford ‡4) undergoing infrapopliteal stent placement with self-expanding nitinol stents for suboptimal angioplasty reported a high technical success (98%) and primary patency rate of 75.5% with a freedom from amputation rate of 88.7% at 2 years [50]. This study supports the feasibility and efficacy of infrapopliteal stenting, specifically in the CLI patient population.…”
Section: Covered Stentssupporting
confidence: 59%
“…Bare nitinol self-expanding stents are currently used to treat suboptimal angioplasty results in infrapopliteal disease. A nonrandomized retrospective study of 53 patients with CLI and infrapopliteal disease (Rutherford ‡4) undergoing infrapopliteal stent placement with self-expanding nitinol stents for suboptimal angioplasty reported a high technical success (98%) and primary patency rate of 75.5% with a freedom from amputation rate of 88.7% at 2 years [50]. This study supports the feasibility and efficacy of infrapopliteal stenting, specifically in the CLI patient population.…”
Section: Covered Stentssupporting
confidence: 59%
“…Although the difference was not significant, the rate was higher in the bypass group. Pomposelli, et al 5) reported that the limb salvage rate at 5 years after bypass was 78%, and those reported by Shah, et al 6) and Higashi 7) were 94%, whereas Iida, et al 8) reported that the rate at 3 years after endovascular treatment was 80%, Donas, et al 9) reported it to be 88.7% after 2 years, and Ferraresi, et al 10) reported it to be 93% after 3 years.…”
Section: Discussionmentioning
confidence: 93%
“…14 The durability of suboptimal infragenicular PTA through stent placement has been reviewed in recent studies. 4,15 In this case, we decided to use a balloon-expandable stent, aiming to its more precise deployment. 16 In the infragenicular region, to avoid restenoses, we considered use of double antiplatelet therapy with clopidogrel and aspirin during the first 4 weeks to be convenient 4 ; some authors go even further and use cilostazol or even anticoagulation if an infrapopliteal stent has been placed.…”
Section: Discussionmentioning
confidence: 99%